Potency of the common: intercultural perspectives about community and individuality - Melville, Gert; Ruta, Carlos Rafael; Carugati, Laura S. (Challenges of life, 2016)
"The central question of the book is as follows: to what extent does the community present a challenge in the life of the individual? Well-known international philosophers, historians, anthropologists, political scientists, theologians and sociologists attempted to find explications by intercultural comparison."--Page [4] of cover
Keywords: Erde; Konferenzschrift -- 10.11.2015-13.11.2015 -- Buenos Aires; Konferenzschrift -- 2015 -- Buenos Aires; Gemeinschaft; Ethnische Gruppe; Südamerika; Kulturelle Identität; Individualität